1984
DOI: 10.3758/bf03332179
|View full text |Cite
|
Sign up to set email alerts
|

The use of intramaze stimuli in the attenuation of the problem-solving deficit of septal animals

Abstract: An attempt was made to ameliorate the deficit in performance shown by septal rats on the Maier three-table task by using either a distinctive visual stimulus insert as a discriminative cue to the route to the daily locus of the food table (Experiment 1) or distinctive visual inserts merely to mark the spatiallocation of each table and the runway leading to that table from the choice point (Experiment 2). When a single stimulus insert consistently identified the food table and the runway to it, regardless of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There is strong evidence that the hippocampus constructs and stores cognitive maps of spatial relationships (O'Keefe and Nadel, 1978;Olton, 1978;Ellen and Wages, 1984;Ellen and Weston, 1983). Rats with damage to the septal forebrain, the hippocampus, or the septo-hippocampal pathway show impaired performance on tasks that require spatial learning such as the Olton eight-arm maze (Olton, 1978;Olton et al, 1979) and the Morris water maze (Sutherland et al, 1982 a).…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that the hippocampus constructs and stores cognitive maps of spatial relationships (O'Keefe and Nadel, 1978;Olton, 1978;Ellen and Wages, 1984;Ellen and Weston, 1983). Rats with damage to the septal forebrain, the hippocampus, or the septo-hippocampal pathway show impaired performance on tasks that require spatial learning such as the Olton eight-arm maze (Olton, 1978;Olton et al, 1979) and the Morris water maze (Sutherland et al, 1982 a).…”
Section: Introductionmentioning
confidence: 99%
“…Atropine sulfate had no effects on the Trial 1 performance of the animals in the cue task group. It has been shown previously that performance on the cue task is not dependent on the utilization of spatial information (Ellen & Wages, 1984). In the cue task, the animals merely have to choose, at the intersection of the Y. the table on which they had been fed during the feeding experience; because this pattern was consistently associated with the feeding experience, the animals merely had to perform a visual discrimination and not rely on the spatial properties of the task to ensure successful performance.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years there has been a focus of attention on the role of limbic forebrain structures in the performance of rats on spatial tasks. Specifically, it has been shown that rats with damage to the septal forebrain, the hippocampus, or their connections are unable to perform successfully on three different spatial tasks: the Olton eight-arm maze (Olton, 1978; Olton, Becker, & Handelmann, 1979), the Morris water maze (Sutherland, Whishaw, & Kolb, 1982), and the Maier three-table problem (Ellen & Wages, 1984; Ellen & Weston, 1983; Rabe & Haddad, 1969).…”
mentioning
confidence: 99%
See 1 more Smart Citation